Hepatitis C virus and liver transplantation - Berenguer, Marina (Springer New York, 2014)
Hepatitis C Virus and Liver Transplantation is designed to provide a comprehensive and state-of-the-art overview of the major issues specific to the field of liver transplantation and hepatitis C virus infection.   The sections of the book have been structured to review the overall scope of issues of recurrent hepatitis C in different complex settings, including retransplantation, HIV-coinfected patients or in the setting of suboptimal graft donors. This book provides up-to-date information on the application of  new therapies to the field of liver transplantation. It provides the most recent data on their efficacy, the management of side effects, as well as the potential interactions and specific problems associated with their use in the transplant setting. Finally, an appraisal of the risks and benefits of using organs from anti-HCV positive donors is presented. This book provides concise and actual materials for  several important topics that are simply not adequately covered by current available literature. Hepatitis C Virus and Liver Transplantation will provide a unique and valuable resource in the field of liver transplantation and will be of great value to Hepatologists, Transplant and Abdominal Surgeons, Oncologists, as well as Fellows and Residents training in these fields.